Analisis Kemampuan Berpikir Kritis Siswa pada Materi Pengukuran Tidak Baku melalui Masalah Realistis - Prameswari, Claudia; Pratiwi, Ajeng Prastiana; Zuliana, Eka (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study aims to analyze the critical thinking skills of grade 2 students of Kedungmutih Elementary School in measurement material using non-standard units through the Indonesian Realistic Mathematics Education (PMRI) approach. This research used a qualitative method with a descriptive approach. The research subjects were grade 2 students, and data collection was done through observation, interviews, tests, and documentation. The results showed that the PMRI approach and the use of nonstandard measuring tools such as the “Who is More” game helped improve students' critical thinking skills. Students are better able to observe, compare, and draw logical conclusions from the measurement activities carried out. Although some students still have difficulties in understanding the concept of instability of nonstandard unit measures, this study shows that learning with the PMRI approach creates a more interactive and meaningful learning atmosphere, which is relevant to everyday life.